2018
DOI: 10.1002/clen.201800093
|View full text |Cite
|
Sign up to set email alerts
|

Achievability of Municipal Solid Waste Compost for Tea Cultivation with Special Reference to Cadmium

Abstract: Municipal solid waste compost (MSWC) is quite often used for soil amendment in agricultural crops and yet little is known about its effect on tea (Camellia sinensis L.) cultivation. This study investigates the effect of MSWC application on cadmium (Cd) concentrations in soil, tea plants, and infusions. Different doses of MSWC are added to soil with two Tocklai vegetative (TV) tea clones (TV1 and TV23) for 2 years in pot experiments. Several fractions of Cd in amended soils, biomass yield, and Cd content in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Research in India has shown that use of MSW compost in tea cultivation can increase tea yield, but also the total Cd concentrations in soil and plant parts. However, average daily intake levels of Cd through tea infusion suggested no health hazard (Karak et al, 2018). Future risk management efforts should include both efforts to achieve better source separation of biodegradable materials in MSW prior to composting, as well as monitoring of Cd and other heavy metals in soils receiving repeated applications of MSW compost over time (Wei et al, 2017;Karak et al, 2018).…”
Section: Compost Qualitymentioning
confidence: 99%
“…Research in India has shown that use of MSW compost in tea cultivation can increase tea yield, but also the total Cd concentrations in soil and plant parts. However, average daily intake levels of Cd through tea infusion suggested no health hazard (Karak et al, 2018). Future risk management efforts should include both efforts to achieve better source separation of biodegradable materials in MSW prior to composting, as well as monitoring of Cd and other heavy metals in soils receiving repeated applications of MSW compost over time (Wei et al, 2017;Karak et al, 2018).…”
Section: Compost Qualitymentioning
confidence: 99%